Glucose-derived porous carbon-coated silicon nanowires as efficient electrodes for aqueous micro-supercapacitors - Devarapalli, Rami Reddy; Szunerits, Sabine; Coffinier, Yannick; Shelke, Manjusha V.; Boukherroub, Rabah (ACS Applied Materials & Interfaces, 2016)
In this study, we report on carbon coating of vertically aligned silicon nanowire (SiNWs) arrays via a simple hydrothermal process using glucose as carbon precursor. Using this process, a thin carbon layer is uniformly deposited on the SiNWs. Under optimized conditions, the coated SiNWs electrode showed better electrochemical energy storage capacity as well as exceptional stability in aqueous system as compared to uncoated SiNWs. The as-measured capacitance reached 25.64 mF/cm(2) with a good stability up to 25000 charging/discharging cycles in 1 M Na2SO4 aqueous solution.
Keywords: carbon coating; glucose precursor; hydrothermal; microsupercapacitors; silicon nanowires